Torsion of Wandering Gallbladder following Colonoscopy - Sean R. Warfe; Hannah Dobson; Matthew K. H. Hong; Weranja K. B. Ranasinghe; Peter R. Thomas; Adam G. Cichowitz (Case Reports in Medicine)
Torsion of the gallbladder is an uncommon condition that may present as an acute abdomen. Its preoperative diagnosis can often be challenging due to its variable presentation, with specific sonographic signs seen infrequently. We describe, to our knowledge, the first case of torsion of a wandering gallbladder following a colonoscopy in a 69-year-old female who presented with acute abdominal pain after procedure. This was discovered intraoperatively, and after a subsequent cholecystectomy, she had an uncomplicated recovery.